1999
DOI: 10.3141/1694-07
|View full text |Cite
|
Sign up to set email alerts
|

Does Travel Information Influence Commuter and Noncommuter Behavior?: Results from the San Francisco Bay Area TravInfo Project

Abstract: Improved information received from public and private advanced traveler information systems can help travelers make more informed decisions, shorten times spent in traffic congestion, and reduce anxiety and stress. The behavioral responses of automobile and transit commuters as well as those of noncommuters to travel information received from radio, television, and telephone are analyzed. The influence of information has seldom been studied in terms of these different users. The data were collected through a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…These findings are consistent with findings from other surveys presented in the literature (Al-Deek, Chandra, & Flick, 2009;Han, Timmermans, Dellaert, & van Raaij, 2008;Khattak, Yim, & Stalker, 1999;Mahmassani, Huynh, Srinivasan, & Kraan, 2003;Mahmassani & Liu, 1999;Roorda & Andre, 2007;Tsirimpa & Polydoropoulou, 2011).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 95%
“…These findings are consistent with findings from other surveys presented in the literature (Al-Deek, Chandra, & Flick, 2009;Han, Timmermans, Dellaert, & van Raaij, 2008;Khattak, Yim, & Stalker, 1999;Mahmassani, Huynh, Srinivasan, & Kraan, 2003;Mahmassani & Liu, 1999;Roorda & Andre, 2007;Tsirimpa & Polydoropoulou, 2011).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 95%
“…Table 4 presents illustrative comparisons of sub-types of automobile commuters in the second Broad Area survey. Note that other statistically rigorous analyses that we have conducted cannot be presented here due to space limitations (e.g., 12,13,18). The purpose here is to integrate the survey results, interpret them using a conceptual model and draw suggestive inferences regarding the impact of information on various types of travel decisions, and the contribution of different information sources to those decisions.…”
Section: Key Resultsmentioning
confidence: 99%
“…Finally, the specific content demanded by travelers needs more attention. Few studies combine knowledge from revealed choice data with stated preference data to find the true information needs of end users (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Hickman and Wilson (1995) question the benefits of real-time transit information on the basis of finding few changes in route choices, travel time, and trip reliability when such information is provided to transit users. Furthermore, transit users tend to make scant use of static information resources such as maps and schedules when they are available (Balcombe and Vance, 1996;Khattak and de Palma, 1997;Khattak et al, 1999). Non-regular users of transit appear to be even more impervious to efforts at transit information dissemination (Abdel-Aty, 2001; Chorus et al, 2006c).…”
Section: Information and Travel Behaviormentioning
confidence: 97%